Pemberdayaan Masyarakat Melalui Pengolaan Sampah dengan Manajemen Bank Sampah untuk Meningkatkan Pendapatan Ekonomi Keluarga - Suwarso Suwarso; Yosi Mulyana Pratiwi; Galih Satriyo; Yudhi Harris Nurdian; Fandi Ahmad; Janoko Janoko; Moehammad Robith Nahdi (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This community empowerment program through waste management using a waste bank system in Bulusan Village, Kalipuro District, Banyuwangi, was implemented to address the increasing volume of household waste and the community’s limited awareness of waste sorting and its economic potential. The program employed a Participatory Action Research (PAR) approach consisting of needs assessment, joint planning, training, and participatory evaluation. The results show a substantial improvement in waste-sorting behavior, increasing from 23% of households before the intervention to 67% after training. Participation in the waste bank also increased from 15 to 58 households. Within the first three weeks of operation, the waste bank collected 126 kg of plastic, 89 kg of paper, and 17 kg of metal, generating an additional collective income of Rp 1,230,000. Training sessions improved managerial and digital recording skills, with 90% of participants successfully using digital forms for waste savings accounts. The program also stimulated positive social change, including increased daily waste separation habits (74%) and enhanced community interaction (67%). These findings align with prior studies (Fitria, 2024; Sudrajat, 2024; Subekti, 2024), confirming that managerial capacity, digitalization, and community participation are key factors for successful waste bank implementation. Overall, the program positively contributed to environmental improvement and household economic income while strengthening community commitment to sustainable waste management.